Perancangan Strip Biosensor untuk Deteksi Gula Darah dan Asam Urat Berbasis Elektrokimia - Retno Maharsi; Vista Sari Afifah; Zikra Maizi; Ading Atma Gamilang; Doni Bowo Nugroho; Amrina Mustaqim (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2026)
Rapid and accurate monitoring of glucose and uric acid levels is essential for the early detection of metabolic disorders such as diabetes mellitus and hyperuricemia. This study aims to develop an electrochemical biosensor strip based on a conductive carbon electrode for the detection of glucose and uric acid using glucose oxidase and uricase enzymes. The strip was designed with a three-electrode configuration on an acrylic substrate, which was selected due to its lower resistance and superior coating stability compared to PVC. The signal detection system employed a transimpedance amplifier circuit using the LM358, integrated with an Arduino Uno. Measurements were performed using artificial blood samples with various glucose concentrations (0–200 mg/dL) and uric acid concentrations (0–12 mg/dL). Calibration results demonstrated a linear relationship between analyte concentration and the output current, with R² values approaching 1. After correction, the glucose strip exhibited 92–100% accuracy and 92–97% precision, while the uric acid strip achieved 76–99% accuracy and 96–97% precision. These findings indicate that the developed biosensor strip provides consistent and reasonably accurate measurements, demonstrating its potential as an economical and portable point-of-care device for monitoring glucose and uric acid.